Karakteristik Kimia Fisik Fluida Mata Air Panas dan Estimasi Temperatur Reservoir di Sekitar Rano Raindang Desa Leilem, Kecamatan Sonder, Kabupaten Minahasa - Asmaul Husna S; Royke Donny Wenas; Cyrke Adfie Netty Bujung; Sixtus Iwan Umboh (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2024)
To meet future energy needs, the Indonesian government has developed alternative energy sources: geothermal energy. Rano Raindang is one of the areas with a geothermal field due to several geothermal manifestations, such as hot springs. This study aims to examine the fluid type, the reservoir temperature estimation, and the functional group of hot springs. The method used is a geoindicator of Na, K, Mg, Cl, SO4, and HCO3, combining spectrophotometry and FTIR spectroscopy. Research results show that the type of hot spring fluid around Rano Raindang with geoindicators Na, K, Mg is immature waters, this is because the type of hot spring fluid around Rano Raindang has undergone a mixing process, while the geoindicators Cl, SO4, HCO3 are bicarbonate (HCO3) types. This corresponds to the results of measurements using FTIR spectroscopy. The estimated reservoir temperature in the area is 193.66 °C and is included in the medium-temperature geothermal system, as the temperature around Rano Raindang is between 125–225 °C. The functional group of hot spring molecules around Rano Raindang has functional groups C=O and O-H.